2020
DOI: 10.5552/drvind.2020.1955
|View full text |Cite
|
Sign up to set email alerts
|

Wood Surface Finishing of Selected Invasive Tree Species

Abstract: Due to their strong renewal power, the invasive tree species are spreading rapidly, especially in abandoned agricultural and forest areas and along traffic routes and water courses. One way of their restriction is the promotion of their use. In our research, we investigated surface finishing of wood of five selected invasive species in Slovenia, Box elder (Acer negundo L.), Black locust (Robinia pseudoacacia L.), Horse-chestnut (Aesculus hippocastanum L.), Honey locust (Gleditsia triacanthos L.) and Chinese su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The impact resistance of a surface finish is influenced by hardness of the substrate as well as the film's brittleness and elasticity. Additionally Pavlič et al [42] recorded the influence of substrate on impact resistance of the coated surfaces. Tesařová et al [43] reported a hypothesis about the relationship between the physical-mechanical properties of lacquers surface finishes and the ultimate tensile stress of free coating films.…”
Section: Impact Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The impact resistance of a surface finish is influenced by hardness of the substrate as well as the film's brittleness and elasticity. Additionally Pavlič et al [42] recorded the influence of substrate on impact resistance of the coated surfaces. Tesařová et al [43] reported a hypothesis about the relationship between the physical-mechanical properties of lacquers surface finishes and the ultimate tensile stress of free coating films.…”
Section: Impact Resistancementioning
confidence: 99%
“…In previous work [27], thermally modified beech wood showed the increased surface hardness of these oil and wax surface finishes. The surface hardness is a property of the coating film, but it was proven that the determined hardness was also influenced by the substrate [42].…”
Section: Hardnessmentioning
confidence: 99%
“…This is consistent with the information provided on the improvement in quality when more topcoat is applied [ 38 ]. The application of a second layer of topcoat increases a coating’s resistance according to earlier experiments on wood samples with coatings made of numerous layers of waterborne varnishes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…For each sample, 10 measurements were taken, and the average values were recorded. The color differences were determined with the delta E parameter, which indicates the total color difference [ 31 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation